Orange-fleshed sweet potato (OFSP)–Cassava composite Gari: Effects of processing variables and Storage on beta-carotene and sensory qualities - Atobrah, Emmanuel Ebo (University of Cape Coast, 2020)
Incorporating orange-fleshed sweet potato (OFSP) into gari could increase the nutritional value of gari. This work sought to improve the nutritional quality of gari by incorporating OFSP into the gari. Multivariate response surface was used for the optimization of the optimum amount of OFSP and the fermentation duration required in producing a good quality gari. The results showed that beta-carotene content increased with increasing fermentation duration and increasing OFSP percentage. However, OFSP amount did not affect the swelling capacity while a longer fermentation period reduced the swelling capacity of the OFSP–cassava composite gari. Incorporation of OFSP into gari lowered its sensory attributes, while attributes such as texture and overall acceptability increased with fermentation duration. Furthermore, the OFSP amount and fermentation duration affected the lightness (L*) and redness (a*) of the gari, but did not influence the yellowness (b*) of the gari. Producing gari by using 90% cassava and 10% OFSP (9:1 ratio of cassava to OFSP) and fermenting for 2.21days gave the best quality gari based on the beta-carotene content of 19.8 µg/ml, swelling capacity of 3.2 and sensory attributes. Moreover, both storage conditions and storage durations influenced the beta-carotene content of the gari but did not affect the swelling capacity, bulk density and colour of OFSP–cassava composite gari significantly. The profit on the OFSP–cassava composite gari was determined to be higher than that of 100% cassava gari. Orange-fleshed sweet potato could therefore be incorporated into gari to improve the vitamin A content of gari and thereby improve the economic status of gari processors.
xi,133p:, ill.
Keywords: orange-fleshed; fermentation; gari